Sensor capacitivo inteligente para monitoramento de escoamentos bifásicos - Santos, Greg José dos (2015)
Two-phase flow is frequently found in industrial activities, for instance in chemical reactors or during oil production and transport, where gas-liquid flow type is the most common. Such flow is characterized by the simultaneous passage of two immiscible fluids in a pipe. The fluids may assume various spatial distributions in a pipe, which are classified into flow regimes. In many cases, the type of flow determines the efficiency and safety of the processes or plants in which they occur. The objective of this work is to develop a smart sensor for real-time monitoring of two-phase flows. Here two important monitoring parameters were selected; the first is the gas void fraction and the second translational bubble velocities. To this aim, a capacitive probe was developed that exploits the difference in electrical permittivity of the phases. In addition, a previously developed electronics have been further developed to make it possible to measure two channels simultaneously and the firmware has been modified for performing the calculation of the two parameters directly in the embedded microcontroller. The response of the capacitive probe depends not only on the volume fraction of the phases, but it also depends on the way they are distributed inside the pipe. In order to account for this, electric field simulations by finite element method were performed to survey the sensor responses. The overall sensor response was validated by static tests and controlled flow experiments in a pilot plant. The measurement results were compared with those obtained by simultaneous measurements with a wire-mesh sensor which was adopted as reference in this study. The results show that the capacitive sensor is able of measuring the parameters satisfactorily. Hence, the sensor can be applied in future work as a simple tool for two-phase flows monitoring.